An investigation into the effects of early propping removal on the deflection of reinforced concrete beams - Rockstroh, Benjamin Andreas (Department of Civil Engineering, 2019)
In today’s fast paced construction industry, there is an ever present need to increase productivity and to complete projects as quickly as possible. Reinforced concrete is a popular and widely used construction material. However it has the unfortunate drawback in that the concrete requires time to set and gain sufficient strength before loads may be applied and the formwork and props can be removed. It is therefore desirable to keep propping times to a minimum. If the propping is removed too early, there is a risk of the member deflecting excessively and exceeding the maximum allowable limits, or in severe cases it could even lead to a structural failure or collapse. The SANS 2001 code provides recommended propping times for beams and slabs, which can be used as a guideline by building contractors and structural designers. These propping times present a universal approach, which does not consider all the factors that affect deflection. This simplified approach may be considered to be conservative as shorter propping durations could be possible without a loss in performance. The aim of this dissertation is to look into the effects of early propping removal on the longterm deflections of concrete members. This was done by modelling the deflection of a typical reinforced concrete beam at different ages of loading, using three code-based deflection calculation methods. The codes that were used are the South African National Standard (SANS), Eurocode (EC2) and American Concrete Institute code (ACI 318). A detailed literature-based investigation was conducted to determine the factors which affect deflection in reinforced concrete members, as well as the theory behind the code-based deflection calculation procedures. This was followed by the modelling of deflections using the abovementioned methods. Three case studies were performed to determine the effects of early propping removal under different scenarios. The first case study only deals with the effects of early age loading on long-term deflection. As an added point of interest, two different concrete mixes were used, made with two different types of cement. The second case study compares the effect that different levels of relative humidity have on the long term deflection at early ages of loading. Lastly, the effects of concrete strength on long-term deflections at early ages of loading was modelled. The results of the first case study indicated that a reduction in propping time is possible without causing excessive deflections. In the second and third case study is was observed that both the relative humidity and concrete strength respectively have an effect on the long term deflection and therefore also influence the propping time. The study concluded that based on the obtained estimated deflection values using the codebased methods, the propping times provided in the SANS 2001 code may in certain applications be conservative. According to the results obtained from the code-based deflection calculation procedures, it is possible to reduce the propping duration. It was suggested that an alternative method should be developed which would allow structural designers to determine the required propping time more accurately.